A Journey of Embedded and Cyber-Physical Systems - Jian-Jia Chen (Springer International Publishing, 2020)
This Open Access book celebrates Professor Peter Marwedel's outstanding achievements in compilers, embedded systems, and cyber-physical systems. The contributions in the book summarize the content of invited lectures given at the workshop “Embedded Systems” held at the Technical University Dortmund in early July 2019 in honor of Professor Marwedel's seventieth birthday.Provides a comprehensive view from leading researchers with respect to the past, present, and future of the design of embedded and cyber-physical systems;Discusses challenges and (potential) solutions from theoreticians and practitioners on modeling, design, analysis, and optimization for embedded and cyber-physical systems;Includes coverage of model verification, communication, software runtime systems, operating systems and real-time computing.